Sistem Rekomendasi Tempat Kuliner Di Kabupaten Xyz Menggunakan Metode Multy-Objective Optimization By Ratio Analysis - Kundika whicak; Tacbir Hendro Pudjiantoro; Puspita Nurul Sabrina (Prosiding SISFOTEK, 2020)
Culinary Tourism is one of the activities that must be visited by tourists when visiting a certain area that has special food. Food is now not just meeting the needs of one's life but has become an art in culinary. Some people have a tendency to visit homogeneous eating places (not varying), this can be caused by several things, including budget (shopping budget), type of food, facilities, location and opening time. Visiting a suitable place to eat is certainly one of the things that need attention, but information about the complete culinary place is still not widely known by tourists and new residents in the regency of XYZ. To determine a culinary place, tourists must really know complete information about a culinary place that they want to visit to suit their wants and needs. By having to make a decision made by tourists to determine the culinary places that will be visited then the construction of a system that aims to support a decision that determines where culinary in accordance with one's wishes in XYZ Regency. The system development will use the method of Multy-Objective Optimization by Ratio Analysis (Moora) and the approach